Effects of wet corn gluten feed and dietary particlesize on ruminal fermentation and milk production - M.L. Sullivan; Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2010)
Wet corn gluten feed (WCGF) was included in 4 diets at 0, 11, 23, and 34% of diet dry matter. Alfalfa hay was used to maintain at least 10% of particles ≥0.71 inches in length (the top screen of the Penn State Particle Separator) in all diets. Ruminal probes were placed in the rumens of 7 ruminally cannulated lactating Holstein dairy cows to measure ruminal pH. As WCGF increased in the diet, dry matter intake and milk production increased quadratically with 23% WCGF supporting the highest feed intake and milk yield. Ruminal pH and milk fat content were similar across all diets.; Dairy Day, 2010, Kansas State University, Manhattan, KS, 2010; Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-129-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1039; Dairy; Alfalfa; Dry matter intake; Milk yield; Wet corn gluten feed